Epigenetics and its role in effecting agronomical traits - Chainika Gupta; Romesh K. Salgotra (Frontiers in Plant Science, 2022)
Climate-resilient crops with improved adaptation to the changing climate are urgently needed to feed the growing population. Hence, developing high-yielding crop varieties with better agronomic traits is one of the most critical issues in agricultural research. These are vital to enhancing yield as well as resistance to harsh conditions, both of which help farmers over time. The majority of agronomic traits are quantitative and are subject to intricate genetic control, thereby obstructing crop improvement. Plant epibreeding is the utilisation of epigenetic variation for crop development, and has a wide range of applications in the field of crop improvement. Epigenetics refers to changes in gene expression that are heritable and induced by methylation of DNA, post-translational modifications of histones or RNA interference rather than an alteration in the underlying sequence of DNA. The epigenetic modifications influence gene expression by changing the state of chromatin, which underpins plant growth and dictates phenotypic responsiveness for extrinsic and intrinsic inputs. Epigenetic modifications, in addition to DNA sequence variation, improve breeding by giving useful markers. Also, it takes epigenome diversity into account to predict plant performance and increase crop production. In this review, emphasis has been given for summarising the role of epigenetic changes in epibreeding for crop improvement.